Adherence to asthma treatments: 'we know, we intend, we advocate'. Issue 1 (February 2015) - Braido, Fulvio; Baiardini, Ilaria; Blasi, Francesco; Pawankar, Ruby; Canonica, Giorgio W.
Abstract : Purpose of review: To highlight the state of the art and the current outlook on the adherence to treatment in asthma, starting from the 'Manifesto on Adherence to asthma treatment in respiratory allergy' endorsed by the World Allergy Organization, Allergic Rhinitis and Its Impact on Asthma and Global Allergy, Asthma European Network, and Interasma. Recent findings: Adherence to the pharmacological treatments of asthma is known to be low: about 50% of those who had been prescribed long-term treatment are nonadherent, at least part of the time. Nonadherence is associated with lack of asthma control, poor health outcomes, and increased costs. The reasons for suboptimal adherence are multifaceted and may be related to the patients, the treatment and asthma features, the physician–patient relationship, and the healthcare resources and facilities. Summary: Taking into account the multidimensional nature of adherence, no single intervention or strategy is per se able to enhance it, but all players involved in the process (government authorities, patient organizations, scientific societies, stakeholders, and others) are called to work together to develop a combined action plan based on the patient's complexity.